Proyecto semilla: “evaluación de sistemas de filtración agua de bajo de costo para consumo humano - Jarrín Pérez, Fernando (2009)
In Ecuador, we have zones without drinking water systems neither waste water treatments, most of them in the rural areas, where digging deep holes is the usual way to extract water from the underground and to treat waste water (septic holes). Septic holes built without the correct techniques could discharge directly to ground water sources, contaminating them, also flooding can cover entirely all deep holes mixing the water inside them, and making impossible to drink this water without the risk of getting a disease. The current project evaluates two household filtration systems; a biologic sand filter, and a ceramic filter, which have prove to remove 99.99% of virus and bacteria. These are easy elaboration, operation and maintenance systems, the production cost is very low, and they’d have an important application in low resources communities like contingency plans in case of flooding. During the experimentation, it has achieved 99.8% fecal coliform removal, and 99.7% E. Coli removal in some cases.